Business Plan Website Laughonthefloor.com - Ariana Hayyulia Rasyid (Jurnal Administrasi Bisnis, 2015)
The rapid development of Information Technology turned out to open the opportunity of E-Commerce. Nowadays, E-Commerce is one of the promising business opportunities. By managing a blog, a blogger can earn a considerable profit. This study aims to determine whether the business on the internet is worth to run, how to design this kind of business, and how much the budget needed to run this business. The business plan is applied to www.laughonthefloor.com by using descriptive analysis method. The data gathered by using literature research and also field research. Www.laughonthefloor.com is running E-Commerce that uses advertising model. Where the main income comes from advertising costs. Keywords: E-Commerce, business plan, web, blog, internet